Rare bird documentation form for Red-necked Phalarope at Big Spirit Lake, 1991 - Schoenewe, Lee A.et al (1991)
Rare bird documentation form for a Red-necked Phalarope at Big Spirit Lake in Dickinson County, IA on September 15, 1991. Epson - sheet feed